2022
DOI: 10.1101/2022.01.04.474997
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elixirs of Life, threats to Human and Environmental Well-being: Assessment of Antibiotic Residues in Raw Meat Sold Within Central Market Kaduna Metropolis, Kaduna State, Nigeria

Abstract: Antibiotics, which are commonly used to treat human illnesses, are also used in animals for therapy, prophylaxis, and growth promotion. Sub-therapeutic antibiotic doses have typically been utilized for the last-mentioned purpose, which has contributed to resistance development. According to scientific data, certain antibiotic applications in food-producing animals can result in antibiotic resistance in intestinal bacteria, which can then be passed to the general population, causing treatment-resistant sickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The world we lived in today is highly mobile, interdependent, and interconnected, giving tremendous opportunities for diseases to spread rapidly [12,13,14,15,20]. Besides, the public has been focusing on new health events caused by microbiological, toxic metals concentration and sudden environmental changes in the recent past [21,22,23,24,25,26,27,28,29]. Thus, this study revealed that the bacteria load was highest in salad and lowest microbial load in fried fish.…”
Section: Discussionmentioning
confidence: 99%
“…The world we lived in today is highly mobile, interdependent, and interconnected, giving tremendous opportunities for diseases to spread rapidly [12,13,14,15,20]. Besides, the public has been focusing on new health events caused by microbiological, toxic metals concentration and sudden environmental changes in the recent past [21,22,23,24,25,26,27,28,29]. Thus, this study revealed that the bacteria load was highest in salad and lowest microbial load in fried fish.…”
Section: Discussionmentioning
confidence: 99%
“…They are extremely carcinogenic and can result in skin, bladder, liver, and lung cancer. Arsenic exposure in humans occurs through the air, food, and water [7,[107][108][109][110]. One of the main contributors to arsenic toxicity in more than 30 nations throughout the world is drinking water [111].…”
Section: Sulphate (So 4 2-mentioning
confidence: 99%
“…Food has an important role in society through affecting people’s lifestyles, health, and habits, as well as being an important aspect of socializing [1, 2, 3, 4, 5, 6]. Today, hotels must pay greater attention to food safety, environmental protection, justice, human rights, and everything else connected to the ethical content of economic operations in the producing world [2, 7, 8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Food poisoning, unlike certain other health disorders, affects every nation, regardless of income or development level [10, 11, 12, 13, 14, 15, 16, 17, 18, 19]. Several studies have found that food-borne diseases impose a remarkable economic as well as quality-of-life burden on society through acute morbidity and chronic sequelae [2, 5, 6, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31]. Food-borne infections cover a wide range of ailments and are an increasing public and environmental health concern across the world.…”
Section: Introductionmentioning
confidence: 99%